Effect of Bumetanide on Facial Nerve Regeneration in Rat Model - Longur, Ecem Sevim; Yiğit, Özgür; Kalaycık Ertugay, Çiğdem; Araz Server, Ela; Adatepe, Turgut; Akakın, Dilek; Orun, Oya; Karagöz Köroğlu, Ayça (Otolaryngology-head and neck surgery, 2021)
We investigated the effects of bumetanide alone and in combination with dexamethasone on facial nerve regeneration in rats with facial paralysis. A prospective controlled animal study. An animal laboratory. Facial paralysis was induced in 32 Wistar rats that we then divided into 4 groups: group 1, control; group 2, bumetanide; group 3, dexamethasone; group 4, bumetanide and dexamethasone. Electroneurography was performed 1, 2, and 4 weeks later, and nerve regeneration was evaluated by electron and light microscopy and Western blotting in week 4. Regarding the comparison between preoperative values and week 4, the latency difference in group 1 (1.25 milliseconds) was significantly higher than those of groups 2 to 4 (0.56, 0.34, and 0.10 milliseconds, respectively; = .001). The latency increment in groups 2 and 3 was higher than that of group 4 ( = .002 and = .046) in week 4, whereas groups 2 and 3 did not differ significantly ( = .291). Amplitude difference was not statistically significant from week 4 among all groups (all .05). The number of myelinated axons was significantly higher in all treatment groups than in the control group ( = .001). Axon number and intensity were significantly higher in group 4 as compared with groups 2 and 3 ( = .009, = .005). After primary neurorrhaphy, dexamethasone and bumetanide alone promoted nerve recovery based on electrophysiologic and histologic measures. Combination therapy was, however, superior.